Implementasi Deteksi Hujan dan Banjir Secara Real Time Monitoring berbasis MQTT Over Websocket Menggunakan Modul ESP32 - Muhammad Rouzikin Annur; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Indonesia is a country traversed by the equator, which means that rainfall in Indonesia is quite high. Rainfall in several areas, one of which is in the city of Malang, is one of the areas that has high rainfall. The uneven road conditions in Malang City make part of the road flooded with water when it rains and some roads that are not flooded are inundated, therefore the authors make a tool that can provide information on the latest conditions on roads prone to rain and floods with standing water by installing a detection tool in the form of a sensor that is connected to the internet so that it can be accessed by the general public. The way this tool works is by detecting rain and water levels on the highway, precisely on roads where floods often occur during heavy rain, then the detection data is sent to the internet so that it can be accessed by users or the general public. The results of this study are expected to be able to help users or the general public find alternative roads when there is rain or a flood of standing water on the highway.